Complementary and alternative medicine among infertile couples - Grygoruk, Cezary; Mrugacz, Grzegorz; Grusza, Grusza (Nursing in the 21st Century, 2013)
COMPLEMENTARY AND ALTERNATIVE MEDICINE AMONG INFERTILE COUPLESAim. Infertility is a growing social problem. It is estimated, that approximately 12-15% of people in reproductive age are suffering from infertility. On the other hand, there is little data on the prevalence of use of complementary and alternative medicine among infertile couples. Therefore, it was decided to conduct a study to determine the frequency of using alternative and complementary medicine by infertile couples.Material and methods. Voluntary and anonymous survey (authors’ questionnaire) was conducted between 06.2011 and 06.2012. The study involved 300 couples treated for infertility.Results. Altogether 216 out of 600 patients applied complementary and alternative medicine during infertility treatment. Herbal medicine, homeopathy and acupuncture were most frequently applied by the studied group of patients.Conclusions. The results of the present study indicated that patients had relatively often used the alternative medicine during infertility treatment. On the other hand, there is still a need to conduct extensive study on the usage of complementary and alternative medicine among infertile couples.